Breastfeeding with primary low milk supply: a phenomenological exploration of mothers’ lived experiences of postnatal breastfeeding support - Caoimhe Whelan; Denise O’Brien; Abbey Hyde (International Breastfeeding Journal)
Abstract Background Most women can produce enough milk to exclusively breastfeed. However, a small cohort are prevented from doing so due to a condition known as primary low milk supply. The aim of the study was to provide new insights into how mothers with this condition experience help and support from professionals, volunteer support groups, and partners. Methods Interpretative phenomenological analysis was used to explore the lived experiences of nine first-time breastfeeding mothers in Ireland who had primary low milk supply. One-hour interviews were conducted over Zoom between April and October 2021. Results Being with Others, one of four superordinate themes identified in this study, concerns the participants’ experiences of receiving professional, voluntary, and partner breastfeeding support. Four sub-themes were identified: Disconnected Encounters, Perceiving Judgement from Others, Being in a Safe Space and Having a Saviour. The encounters of participants with healthcare professionals revealed a lack of rapport, intrusive hands-on support, poor perceived quality of breastfeeding support and a heightened sensitivity to language and tone. Participants expressed that they valued empathy and emotional support from lactation professionals as much as they valued skilled lactation support. Furthermore, participants appeared to experience an enhanced motherhood self-identity and self-acceptance through seeing their experiences mirrored in the experiences of other mothers with primary low milk supply in specialist low milk supply-specific support groups. Conclusion The interactions that mothers with primary low milk supply have with various others in their world (healthcare professionals, lactation consultants, volunteer breastfeeding supporters, and partners) can shape how they view themselves and can have a profound impact on their breastfeeding journey. There is a need for greater knowledge and understanding among healthcare professionals of the phenomenon of primary low milk supply so that women suspected of having the condition may receive appropriate support. Where possible, mothers with primary low milk supply should be directed to specialist breastfeeding support groups.